Scour and Erosion 2016
DOI: 10.1201/9781315375045-38
|View full text |Cite
|
Sign up to set email alerts
|

Effect of bottom roughness on sediment transport due to streaming beneath linear propagating waves with an angle of attack on current

Abstract: The effect of bottom roughness on sediment transport due to three-dimensional wave-induced streaming in the seabed boundary layer has been investigated for following and opposing linear propagating waves and current where the wave propagation forms a non-zero angle with the current. Visualizations are given by mean Eulerian wave-averaged suspended flux profiles, as well as the time series of bed shear stress over a wave period. The bedload transport rate along with suspended flux and total sediment transport r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…It was found that for the medium-sized sand grains, streaming can enhance onshore sediment rates significantly. For fine sand, streaming can reverse the direction of net transport from offshore to onshore direction Afzal et al (2016). investigated sediment transport in the bottom boundary layer, where linear waves propagated at an angle with the current over various bottom roughnesses.…”
mentioning
confidence: 99%
“…It was found that for the medium-sized sand grains, streaming can enhance onshore sediment rates significantly. For fine sand, streaming can reverse the direction of net transport from offshore to onshore direction Afzal et al (2016). investigated sediment transport in the bottom boundary layer, where linear waves propagated at an angle with the current over various bottom roughnesses.…”
mentioning
confidence: 99%